The use of digital technology in non-pharmacological cognitive and psychosocial interventions for people with dementia and mild cognitive impairment: A scoping review - Ana B. Vivas; Imran Khan; Qarin Lood; Pierre Gander; Mia Dong; Simon Nielsen; Robert Lowe (PLoS ONE, 2026)
Objective The purpose of this scoping review was to identify, geographically map, and understand what and how novel digital technologies are being used for providing cognitive training and psychosocial interventions that aim at preserving cognitive and everyday function, and improving well-being, in dementia patients, and persons with Mild Cognitive Impairment (MCI). Design Studies were identified across seven databases (EMBASE, Scopus, CINAHL Complete, PubMed, Dimensions, APA PsychInfo) dating from 2012-Dec 2025, and one hundred and fourteen met the inclusion criteria. We followed the Joanna Briggs Institute guidelines and the framework. Screening was undertaken according to the PRISMA-SCR guidelines and involved 7 reviewers across stages. Results This review analysed 114 articles and uncovered 8 main categories of digital technology focused on intervention delivery methods that adhered to our inclusion/exclusion criteria. Of those, gamified technology, apps, and web-based approaches were most commonly studied. An emerging technology identified was virtual reality based delivery. There was great heterogeneity in the evidence of effectiveness of the technology-based interventions on cognitive, functional and wellbeing outcomes as reported in the studies included here. There was also great variability across the studies in how the interventions were designed and implemented and what and how many outcomes were measured. Conclusions This review supports that the majority of the digital interventions for cognitive and psychosocial interventions are being developed and tested for administration under real-time supervision by a trained professional and not for unsupervised home environments. Notwithstanding, technology suitable for home use such as gamified tasks, apps and web/internet-based approaches were found to be the most prominent interfaces for digital interventions. Virtual reality (VR) based interventions, e.g., using simple headsets, must also be considered as intervention tools with high potential for home use mitigating issues of limited mobility through cognitive-physical training (combining physical – exergaming – and cognitive training).